What happens after they survive? The role of anticoagulants and antiplatelets in IVC injuries - Niels D Martin; Patrick M Reilly; Allyson M Hynes; Dane R Scantling; Shyam Murali; Bradford C Bormann; Jasmeet S Paul; Mark J Seamon (Trauma Surgery & Acute Care Open)
Background Venous thromboembolism (VTE) after an inferior vena cava (IVC) injury is a devastating complication. Current practice involves variable use of anticoagulation and antiplatelet (AC/AP) agents. We hypothesized that AC/AP can reduce the incidence of VTE and that delayed institution of AC/AP is associated with increased VTE events.Methods We retrospectively reviewed IVC injuries cared for at a large urban adult academic level 1 trauma center between January 1, 2008 and December 31, 2020, surviving 72 hours. Patient demographics, injury mechanism, surgical repair, type and timing of AC, and type and timing of VTE events were characterized. Postoperative AC status during hospital course before an acute VTE event was delineated by grouping patients into four categories: full, prophylactic, prophylactic with concomitant AP, and none. The primary outcome was the incidence of an acute VTE event. IVC ligation was excluded from analysis.Results Of the 76 patients sustaining an IVC injury, 26 were included. The incidence of a new deep vein thrombosis distal to the IVC injury and a new pulmonary embolism was 31% and 15%, respectively. The median onset of VTE was 5 days (IQR 1–11). Four received full AC, 10 received prophylactic AC with concomitant AP, 8 received prophylactic AC, and 4 received no AC/AP. New VTE events occurred in 0.0% of full, in 30.0% of prophylactic with concomitant AP, in 50.0% of prophylactic, and in 50.0% without AC/AP. There was no difference in baseline demographics, injury mechanisms, surgical interventions, and bleeding complications.Discussion This is the first study to suggest that delay and degree of antithrombotic initiation in an IVC-injured patient may be associated with an increase in VTE events. Consideration of therapy initiation should be performed on hemostatic stabilization. Future studies are necessary to characterize the optimal dosing and temporal timing of these therapies.Level of evidence Therapeutic, level 3.